2022
DOI: 10.1111/1750-3841.16025
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of chitosan and garlic against Salmonella spp., Escherichia coli O157:H7, and Listeria monocytogenes in hummus during storage at various temperatures

Abstract: The study aimed to evaluate the antimicrobial activity of 0.5 or 1% (w/w) chitosan and 1% (w/w) garlic against Salmonella spp., Escherichia coli O157:H7 and Listeria monocytogenes in hummus dip stored at 4, 10, or 25°C for 28, 21, or 7 days, respectively. In hummus without garlic, at all storage temperatures and storage periods, 0.5% chitosan decreased Salmonella spp., E. coli O157:H7, and L. monocytogenes by 0.9–2.3, 0.6–2.3, and 0.9–1.3 log CFU/g, respectively. In comparison, 1% chitosan decreased the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…It can be concluded that garlic addition reduced the sensorial acceptability of the hummus samples probably due its strong and sharp flavor and odor, but its combination with other antimicrobials, mainly vinegar or both vinegar and natamycin, helped reduce or mask the effect of garlic and improved its acceptability. This result agrees with another study that showed that when minced fresh garlic was added to hummus, a lower level of acceptance regarding the flavor was noted compared to the control [44]. Moreover, Khoshtinat et al (2022) concluded that garlic cannot be used directly in salad dressing production due to its intense odor [89].…”
Section: Sensorial Analysissupporting
confidence: 87%
See 3 more Smart Citations
“…It can be concluded that garlic addition reduced the sensorial acceptability of the hummus samples probably due its strong and sharp flavor and odor, but its combination with other antimicrobials, mainly vinegar or both vinegar and natamycin, helped reduce or mask the effect of garlic and improved its acceptability. This result agrees with another study that showed that when minced fresh garlic was added to hummus, a lower level of acceptance regarding the flavor was noted compared to the control [44]. Moreover, Khoshtinat et al (2022) concluded that garlic cannot be used directly in salad dressing production due to its intense odor [89].…”
Section: Sensorial Analysissupporting
confidence: 87%
“…Overall, the lowest TAC count or highest log reduction was mainly recorded for GVN compared to all the other treatments during the test days. Several studies showed that combining antimicrobials has more effect against different types of microorganisms in hummus and ready-to-eat food due to the wider spectrum of activity and synergistic activity of antimicrobials such as the combination of potassium sorbate and sodium metabisulfite [10], natamycin, and chitosan-based films [15], natamycin and chitosan [43], garlic and chitosan [44], citric acid and garlic [9]. When the same thymol and carvacrol mixture was used at a higher concentration of 0.8%, a higher effectiveness was achieved in controlling TAC counts in marinated beef (1.1-1.3 logs reduction) [17] and marinated chicken (2.9-3 logs reduction) [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations